Modal Parameters Identification Method Based on Symplectic Geometry Model Decomposition - Hang Jin; Jianhui Lin; Xieqi Chen; Cai Yi (Shock and Vibration)
This paper proposes a novel method of structural system modal identification, where the iterative method is introduced in symplectic geometric model decomposition (SGMD). The proposed method can decompose the measured response into finite symplectic geometric components and identify the modal parameters of time-invariant structures and the instantaneous frequency of time-variant system through each symplectic geometric component. To obtain the shape information of the structural model, the SGCs of the same frequency at different measuring points are subjected to singular value decomposition (SVD). Both simulated data verification and measured data verification were used to verify if the method proposed in this article is effective for time-invariant system and time-variant system identification. For the simulated data, we study on a structural system which is set up with time-variant stiffness and time-invariant system. The measured vibration data of beam structure and time-variant wheel-rail coupling system were also tested and varied. Compared with the results of empirical model decomposition, the proposed method is capable of identifying instantaneous frequencies with better accuracy.